Headwater Capture Evidenced by Paleo-Rivers Reconstruction and Population Genetic Structure of the Armored Catfish (Pareiorhaphis garbei) in the Serra do Mar Mountains of Southeastern Brazil - Lima, Sergio M. Q.; Berbel-Filho, Waldir M.; Araújo, Thais F. P.; Lazzarotto, Henrique; Tatarenkov, Andrey; Avise, John C. (Frontiers in Genetics, 2017)
Paleo-drainage connections and headwater stream-captures are two main historical processes shaping the distribution of strictly freshwater fishes. Recently, bathymetric-based methods of paleo-drainage reconstruction have opened new possibilities to investigate how these processes have shaped the genetic structure of freshwater organisms. In this context, the present study used paleo-drainage reconstructions and single-locus cluster delimitation analyses to examine genetic structure on the whole distribution of Pareiorhaphis garbei, a ‘near threatened’ armored catfish from the Fluminense freshwater ecoregion in Southeastern Brazil. Sequences of two mitochondrial genes, (cytochrome b and cytochrome c oxidase subunit 1) were obtained from five sampling sites in four coastal drainages: Macaé (KAE), São João (SJO), Guapi-Macacu (GAC and GMI), and Santo Aleixo (SAL). Pronounced genetic structure was found, involving ten haplotypes for cytB and six for coi, with no haplotypes shared between localities. Coalescent-based delineation methods as well as distance-based methods revealed genetic clusters corresponding to each sample site. Paleo-drainage reconstructions showed two putative paleo-rivers: an eastern one connecting KAE and SJO; and a western one merging in the Guanabara Bay (GAC, GMI, and SAL). A disagreement was uncovered between the inferred past riverine connections and current population genetic structure. Although KAE and SJO belong to the same paleo-river, the latter is more closely related to specimens from the Guanabara paleo-river. This discordance between paleo-drainage connections and phylogenetic structure may indicate an ancient stream-capture event in headwaters of this region. Furthermore, all analyses showed high divergence between KAE and the other lineages, suggesting at least one cryptic species in the latter, and that the nominal species should be restricted to the Macaé river basin, its type locality. In this drainage, impacts such as the invasive species and habitat loss can be especially threatening for such species with a narrow range. Our results also suggest that freshwater fishes from headwaters in the Serra do Mar mountains might have different biogeographical patterns than those from the lowlands, indicating a complex and dynamic climatic and geomorphological history.